STRUCTURAL DESIGN OF ARCAMANIK APARTMENT AND SHOPPING CENTRE - Louis - Nim: 15014160 , Howard
Arcamanik Apartment and Shopping Centre is a building with one stop living concept located in Arcamanik. This building consists of 3 levels of basement, 4 leves of shopping centre, and 22 levels of apartment. Structural design for Arcamanik Apartment and Shopping Centre uses dual structural systems which are special moment frame and special shear-walled frame according to SNI 1726:2012. This building will also be using reinforced concrete as material according to SNI 2847:2013. Structure will be modelled with ETABS for analysis. Structure will also be designed against earthquake force in Bandung. Analysis will be conducted using two step method where the upper structure designed with reponse spectrum analysis and the lower structure designed with equivalent lateral forces. This building will also be designed against diaphragm forces in reponse to the earthquake lateral loading. Structural elements such as beam, slab, column, and shear wall will be designed as the output of this design process.